Electrode, secondary battery, and electronic device

CN118661296BActive Publication Date: 2026-10-09NINGDE AMPEREX TECHNOLOGY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280090777.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2026-10-09
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

[0003]锂离子电池的电极中常会添加导电剂来提高电极的导电效果,但是在电池经过长循环的情况下,电极的导电效果降低,从而引起极化增大,进而出现循环衰减的问题

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118661296B_ABST
    Figure CN118661296B_ABST
Patent Text Reader

Abstract

The embodiment of the present application provides an electrode, a secondary battery and an electronic device, the electrode comprising: an electrode active material layer, the electrode active material layer comprising an electrode active material and a conductive agent, wherein the conductive agent comprises carbon nanotube clusters, the carbon nanotube clusters are composed of a plurality of carbon nanotube units arranged in a bundle, and the diameter of the carbon nanotube clusters is >0.2 mu m. The electrode has good conductive effect, can improve the charging rate of the battery cell, and can reduce the polarization in the cycle process of the battery cell, and reduce the cycle attenuation problem of the battery cell caused by polarization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and more specifically, to an electrode, a secondary battery, and an electronic device. Background Technology

[0002] Lithium-ion batteries are widely used in digital electronic products, energy storage, drones, power tools, electric vehicles and other products due to their high energy density, long cycle life, high safety and fast charging capabilities.

[0003] Conductive agents are often added to the electrodes of lithium-ion batteries to improve their conductivity. However, after long-term cycling, the conductivity of the electrodes decreases, leading to increased polarization and subsequent cycle degradation.

[0004] Therefore, improving the conductivity of electrodes is a problem that needs to be solved in this field. Summary of the Invention

[0005] This application provides an electrode, a secondary battery, and an electronic device. The electrode has good conductivity, which can improve the charging rate of the battery cell and reduce polarization during battery cell cycling, thereby reducing the cycle degradation problem caused by polarization.

[0006] A first aspect of this application provides an electrode, comprising: an electrode active material layer, the electrode active material layer comprising an electrode active material and a conductive agent.

[0007] The conductive agent includes carbon nanotube clusters, which are composed of multiple bundled carbon nanotube units, and the diameter of the carbon nanotube clusters is >0.2μm.

[0008] According to this application, the electrode active material layer includes carbon nanotube clusters as conductive agents. The carbon nanotube clusters have a structure composed of multiple bundled carbon nanotube units with a diameter greater than 0.2 μm. By forming a long-range conductive network in the electrode active material layer, the electron transport path can be improved, thereby giving the electrode a good conductivity, increasing the charging rate of the battery cell, reducing polarization during battery cell cycling, and thus reducing the cycle decay problem caused by polarization, thereby improving the battery cell's service life.

[0009] In some embodiments of this application, the carbon nanotube clusters constitute 0.05% to 5% by mass in the electrode active material layer.

[0010] In some embodiments of this application, the average diameter d of the carbon nanotube unit satisfies 3nm≤d≤40nm;

[0011] Optionally, the average diameter d of the carbon nanotube unit satisfies 5nm ≤ d ≤ 20nm;

[0012] Optionally, the average diameter d of the carbon nanotube unit satisfies 5nm ≤ d ≤ 10nm.

[0013] In some embodiments of this application, the carbon nanotube unit is a multi-walled carbon nanotube unit.

[0014] In some embodiments of this application, the average diameter D of the carbon nanotube clusters is ≥0.5 μm;

[0015] Optionally, the average diameter D of the carbon nanotube cluster satisfies 0.5μm≤D≤3μm.

[0016] In some embodiments of this application, the average length L of the carbon nanotube clusters is ≥3 μm;

[0017] Optionally, the average length L of the carbon nanotube cluster is ≥ 5 μm;

[0018] Optionally, the average length L of the carbon nanotube cluster satisfies 5μm≤L≤30μm.

[0019] In some embodiments of this application, the particle size Dv50 of the electrode active material and the average length L of the carbon nanotube cluster satisfy: L≥0.2×Dv50.

[0020] In some embodiments of this application, the conductive agent further includes a second conductive agent, which may include one or more of conductive carbon black, acetylene black, discrete carbon nanotubes, carbon fibers, Ketjen black, and graphene, and the second conductive agent has a mass percentage of 0.05% to 5% in the electrode active material layer.

[0021] In some embodiments of this application, the electrode active material layer further includes a binder, wherein the binder comprises 0.5% to 10% by mass in the electrode active material layer.

[0022] In some embodiments of this application, the porosity k of the electrode active material layer satisfies 10% ≤ k ≤ 35%;

[0023] Optionally, the porosity k of the electrode active material layer satisfies 15% ≤ k ≤ 30%.

[0024] In some embodiments of this application, the porosity k of the electrode active material layer, the average length L and the average diameter D of the carbon nanotube cluster satisfy: L / D×k≥0.5, and optionally, 0.8≤L / D×k≤1.6.

[0025] A second aspect of this application provides a secondary battery, comprising: a positive electrode, a negative electrode, a separator, and an electrolyte;

[0026] Wherein, at least one of the positive electrode and the negative electrode is an electrode according to any embodiment of the first aspect.

[0027] In some embodiments of this application, the positive electrode is the electrode according to any embodiment of the first aspect.

[0028] In some embodiments of this application, the resistance of the positive electrode of the secondary battery is R0 when it is at 0% SOC, and the resistance of the positive electrode of the secondary battery is R when it is at 100% SOC. 100 ,

[0029] Among them, R0 and R 100 Satisfy: (R0-R 100 ) / R0≤30%.

[0030] A third aspect of this application provides an electronic device, comprising: a secondary battery according to any embodiment of the second aspect. Attached Figure Description

[0031] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.

[0032] Figure 1 Low-magnification scanning electron microscope image of the electrode provided in the embodiment of this application.

[0033] Figure 2 High-magnification scanning electron microscope image of the electrode provided in the embodiment of this application. Detailed Implementation

[0034] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0035] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in the description of this application is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms "comprising" and "having," and any variations thereof, in the description, claims, and accompanying drawings of this application are intended to cover non-exclusive inclusion. The terms "first," "second," etc., in the description, claims, or accompanying drawings of this application are used to distinguish different objects, not to describe a specific order or hierarchy.

[0036] In this application, the reference to "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment that is mutually exclusive with other embodiments.

[0037] In the description of this application, it should be noted that, unless otherwise expressly specified and limited, the terms "installation," "connection," "linking," and "attachment" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal communication between two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.

[0038] In this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, in this application, the character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0039] In the embodiments of this application, the same reference numerals denote the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments. It should be understood that the thickness, length, width, and other dimensions of various components in the embodiments of this application shown in the accompanying drawings, as well as the overall thickness, length, width, and other dimensions of the integrated device, are merely illustrative and should not constitute any limitation on this application.

[0040] In this application, "multiple" means two or more (including two).

[0041] In this application, the battery cell may include a lithium-ion secondary battery cell, a lithium-ion primary battery cell, a lithium-sulfur battery cell, a sodium-lithium-ion battery cell, a sodium-ion battery cell, or a magnesium-ion battery cell, etc., and the embodiments of this application are not limited thereto. The battery cell may be cylindrical, flat, cuboid, or other shapes, etc., and the embodiments of this application are not limited thereto.

[0042] Currently, a major development direction for lithium-ion batteries is to improve their charge-discharge efficiency and cycle life, among which electrode polarization is a significant factor restricting their development.

[0043] Generally speaking, the better the conductivity of an electrode, the smaller its polarization. Therefore, improving the conductivity of an electrode is an effective way to reduce electrode polarization. In this regard, existing technologies often add conductive agents to the electrode. However, excessive amounts of conductive agents can affect the energy density of the electrode. Therefore, a conductive agent that provides good conductivity in a small amount is needed. Currently, the most commonly used types of conductive agents include carbon black, graphene, and carbon nanotubes. Carbon nanotubes are further divided into multi-walled carbon nanotubes and single-walled carbon nanotubes.

[0044] Carbon black conducts electricity primarily through point contact with the electrode active material, while graphene conducts electricity through surface contact, and carbon nanotubes conduct electricity through line contact. The conductive network formed by point contact is unstable; changes in the volume of the electrode active material during charging and discharging disrupt the original conductive network, resulting in decreased conductivity. While the conductive network formed by surface contact is more stable, it affects the electrolyte migration rate within the electrode and is difficult to form long-range conductive networks and ion transport pathways. The conductive network formed by line contact overcomes these drawbacks and significantly improves electrode conductivity. However, although single-walled carbon nanotubes have high conductivity, their structure is easily damaged during charging and discharging, reducing conductivity. While multi-walled carbon nanotubes have a more stable structure, they are easily broken during dispersion, failing to form complete long-range conductive paths, thus limiting their applications.

[0045] In response to this issue, the inventors, through in-depth consideration and extensive experimentation, have developed an electrode that uses carbon nanotube clusters with a diameter greater than 0.2 μm as a conductive agent. These carbon nanotube clusters can form a stable long-range conductive network within the electrode's active material layer, improving electron transport paths and thus giving the electrode excellent conductivity. When applied to secondary batteries, this reduces the impact of electrode polarization on the battery cell, resulting in faster charge / discharge rates and longer cycle life.

[0046] electrode

[0047] A first aspect of this application provides an electrode, comprising: an electrode active material layer, the electrode active material layer comprising an electrode active material and a conductive agent.

[0048] The conductive agent includes carbon nanotube clusters, which are composed of multiple bundled carbon nanotube units, and the diameter of the carbon nanotube clusters is >0.2μm.

[0049] According to this application, the electrode active material layer includes carbon nanotube clusters as conductive agents. The carbon nanotube clusters have a structure composed of multiple bundled carbon nanotube units with a diameter greater than 0.2 μm. By forming a long-range conductive network in the electrode active material layer, the electron transport path can be improved, thereby giving the electrode a good conductivity, increasing the charging rate of the battery cell, reducing polarization during battery cell cycling, and thus reducing the cycle decay problem caused by polarization, thereby improving the battery cell's service life.

[0050] In the context of this application, "carbon nanotube cluster" refers to a structure composed of multiple carbon nanotube units arranged in a bundle and bonded together, wherein the long axes of the carbon nanotube units are parallel to each other and have a diameter > 0.2 μm, such as... Figure 1 , 2 The image shown is a scanning electron microscope (SEM) image of the electrodes at different magnifications in some embodiments of this application. Figure 1 The presence of the aforementioned carbon nanotube clusters in the electrode is clearly visible. Figure 2 As can be seen, the carbon nanotube cluster is composed of multiple carbon nanotube units arranged in bundles and bonded together. Prior to this application, carbon nanotubes have been used as conductive agents in electrode active material layers. Due to the extremely high aspect ratio and specific surface area of ​​carbon nanotubes, they are prone to aggregation. Therefore, conventional carbon nanotube raw materials are usually provided in the form of aggregates. According to the relevant teachings of this application, in order to exert the conductive effect of carbon nanotubes, it is required that carbon nanotubes be uniformly dispersed in the electrode active material layer in the form of single carbon nanotube units. To this end, a dispersion of carbon nanotube conductive agent in a dispersant is generally prepared first. The dispersion conditions used allow the carbon nanotube units to be fully dispersed in the dispersant, and carbon nanotube clusters will not form or will not form at all (i.e., even if carbon nanotube clusters similar to those provided in this application are unintentionally formed, their content is very low) in the dispersion. Then, such a carbon nanotube conductive agent dispersion is thoroughly mixed with the electrode active material and other additives to form an electrode active material slurry. The electrode active material slurry is then coated and dried to form an electrode active material layer. As described above, in the electrode active material layer thus formed, carbon nanotubes are basically uniformly dispersed in the electrode active material layer in the form of carbon nanotube units, and there are no or basically no carbon nanotube clusters with a diameter > 0.2 μm (i.e., even if carbon nanotube clusters similar to those provided in this application are unintentionally formed, their mass percentage in the electrode active material layer is much less than 0.05%).

[0051] According to this application, the carbon nanotube clusters have a diameter greater than 0.2 μm and possess high mechanical strength, enabling them to form a stable conductive network within the electrode active material layer. Regardless of whether the carbon nanotube units constituting the clusters are single-walled or multi-walled carbon nanotubes, this conductive network is not easily affected by volume changes in the active material during cell charging and discharging. Simultaneously, the conductive network can suppress volume changes in the electrode active material during charging and discharging, thus preventing cracks in the active material. Even if cracks do appear, the carbon nanotube clusters can penetrate the cracks and connect to the active material, ensuring the normal pathway of the conductive network. Furthermore, the presence of the conductive network can suppress the peeling of the active material from the current collector, improving electrode adhesion and resulting in excellent electrode conductivity.

[0052] Furthermore, when large-diameter carbon nanotube clusters are dispersed in the electrode active material slurry, their structure is less prone to bending and entanglement, and due to their high strength, they are also less likely to break. This results in a stable long-range conductive network, giving the electrode good conductivity. If the diameter of the carbon nanotube clusters is too small, their high flexibility may cause them to agglomerate in the electrode active material slurry or become entangled on the surface of the electrode active material, thus affecting the formation of the long-range conductive network and the conductivity of the electrode.

[0053] In some embodiments, the carbon nanotube clusters constitute 0.05% to 5% by mass in the electrode active material layer.

[0054] In some of the above embodiments, due to the excellent conductivity of the carbon nanotube clusters, a relatively small amount added to the electrode active material layer can form a good long-range conductive network, thereby increasing the content of electrode active material in the electrode active material layer and thus improving the energy density of the electrode. Furthermore, although the conductivity of the electrode improves with increasing amount of carbon nanotube clusters in the electrode active material layer, the amount added should not be too high. This is because excessive addition will lead to a relative decrease in the content of electrode active material. Additionally, because carbon nanotube clusters have high strength and form a conductive network in the electrode active material layer, excessive addition will result in excessively high strength of the electrode active material layer, making subsequent electrode reprocessing, such as winding, unsuitable. Therefore, in some embodiments of this application, the mass percentage of carbon nanotube clusters in the electrode active material layer can be controlled to be between 0.05% and 5%. For example, the mass percentage of carbon nanotube clusters in the electrode active material layer can be 0.05%, 0.1%, 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or within any of the above values.

[0055] In some embodiments, the average diameter d of the carbon nanotube unit satisfies 3nm ≤ d ≤ 40nm. For example, the average diameter of the carbon nanotube unit can be 3nm, 4nm, 5nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 25nm, 30nm, 35nm, 40nm, or within any of the above values.

[0056] In some of the above embodiments, carbon nanotube clusters are formed by the interconnection of carbon nanotube units. When the average diameter of the carbon nanotube units is too small, during the preparation of carbon nanotube clusters, the small-diameter carbon nanotube units are relatively soft and easily clump together with other carbon nanotube units, making it difficult to obtain carbon nanotube clusters with sufficient strength and a diameter greater than 0.2 μm. Conversely, when the average diameter of the carbon nanotube units is too large, the large-diameter carbon nanotube units are prone to deformation or even breakage during the preparation of carbon nanotube clusters, making it difficult to obtain carbon nanotube clusters with a length that meets the requirements for forming a long-range conductive network, or even making it impossible to obtain carbon nanotube clusters at all. Therefore, the average diameter d of the carbon nanotube units in the carbon nanotube cluster satisfies 3 nm ≤ d ≤ 40 nm, preferably 5 nm ≤ d ≤ 20 nm, and more preferably 5 nm ≤ d ≤ 10 nm.

[0057] It should be noted that, unless otherwise specified, the average diameter d of the carbon nanotube units in the carbon nanotube clusters described in this application refers to the average diameter of the first 100 carbon nanotube units with larger diameters and the last 100 carbon nanotube units with larger diameters when the prepared electrode is observed by scanning electron microscopy (SEM).

[0058] In some embodiments, the carbon nanotube unit is a multi-walled carbon nanotube unit. Since single-walled carbon nanotubes can be described as seamless hollow cylinders formed by rolling up a single layer of graphene sheets, their diameter is typically 1 to 2 nm. Larger diameter single-walled carbon nanotubes lead to structural instability and an increased number of defects. Furthermore, the length of single-walled carbon nanotubes is typically in the micrometer range, resulting in a high aspect ratio and thus strong flexibility. During the preparation of carbon nanotube clusters, they are prone to agglomeration and entanglement, making it difficult to obtain carbon nanotube clusters with a diameter greater than 0.2 μm. On the other hand, the inventors have found that when carbon nanotube clusters composed of single-walled carbon nanotube units are applied to electrode active material slurries, they easily become entangled with other carbon nanotube clusters or on the surface of the electrode active material, thereby affecting the conductivity of the electrode. Multi-walled carbon nanotubes can be considered as concentric arrangements of single-walled carbon nanotubes, i.e., tubular structures formed by seamlessly rolling up multiple layers of graphene sheets. They generally have a large diameter and possess considerable strength, making them less prone to bending, twisting, kinking, or buckling. Therefore, they are less likely to clump or become entangled, making it easier to obtain carbon nanotube clusters with a diameter greater than 0.2 μm. Furthermore, carbon nanotube clusters composed of multi-walled carbon nanotube units are more likely to form a conductive network in the electrode active material layer, improving the electrode's conductivity. Therefore, in some embodiments according to this application, carbon nanotube clusters obtained by combining multi-walled carbon nanotube units are preferably used as conductive agents.

[0059] It is also worth mentioning that single-walled carbon nanotubes have a more complex manufacturing process than multi-walled carbon nanotubes. Therefore, compared with the high yield and high cost of multi-walled carbon nanotubes, using multi-walled carbon nanotube units to form carbon nanotube clusters can effectively save costs.

[0060] In some embodiments, the average diameter D of the carbon nanotube cluster is ≥ 0.5 μm. For example, the average diameter of the carbon nanotube cluster can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, or within any of the above values.

[0061] In the electrode active material layer, when the average diameter D of the carbon nanotube cluster is ≥0.5μm, its strength is high and it is not easy to get entangled with other carbon nanotube clusters or electrode active materials. It can form a long-range conductive network. Moreover, the larger diameter carbon nanotube clusters can effectively prevent the influence of the volume change of the electrode active material on the conductive network. This allows the conductive network to be maintained efficiently during the charging and discharging process of the battery cell, thereby ensuring smooth electron conduction, reducing polarization, and improving electrical performance.

[0062] More preferably, the average diameter D of the carbon nanotube cluster satisfies 0.5 μm ≤ D ≤ 3 μm. This is because if the diameter of the carbon nanotube cluster is too large, it is prone to agglomeration, which requires adding more carbon nanotube clusters to uniformly disperse them in the electrode active material layer to form a conductive network, thereby affecting the energy density of the electrode. Therefore, the diameter of the carbon nanotube cluster should not be too long.

[0063] It should be noted that, unless otherwise specified, the average diameter D of the carbon nanotube clusters mentioned in this application refers to the average diameter of the first 100 carbon nanotube clusters with larger diameters and the last 100 carbon nanotube clusters with larger diameters when the prepared electrode is observed by SEM.

[0064] In some embodiments, the average length L of the carbon nanotube cluster is ≥ 3 μm. For example, the average length of the carbon nanotubes can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 25 μm, 30 μm, or within any range of the above values.

[0065] In some of the above embodiments, in order to form a long-range conductive network in the electrode active material layer, the average length of the carbon nanotube clusters can be ≥3μm. It should be noted that, for those skilled in the art, the average length of the carbon nanotube clusters can be adjusted accordingly based on the thickness of the electrode active material layer and the particle size of the electrode active material. Generally speaking, the longer the average length, the easier it is to form a long-range conductive network. Therefore, more preferably, the average length L of the carbon nanotube clusters is ≥5μm. However, if the average length is too long, agglomeration may easily occur, forming particle scratches or electrode bump instability during electrode preparation, which is not conducive to further processing and utilization of the electrode. Therefore, most preferably, the average length L of the carbon nanotube clusters satisfies 5μm≤L≤30μm.

[0066] It should be noted that, unless otherwise specified, the average length L of the carbon nanotube clusters mentioned in this application refers to the average length of the first 100 carbon nanotube clusters with longer lengths and the last 100 carbon nanotube clusters with longer lengths when the prepared electrode is observed by SEM.

[0067] In some embodiments, the particle size Dv50 of the electrode active material and the average length L of the carbon nanotube cluster satisfy: L≥0.2×Dv50.

[0068] In some of the above embodiments, the relationship between the particle size of the electrode active material and the average length of the carbon nanotube cluster is further defined. It can be understood that when the particle size of the electrode active material is larger, the conductive network connecting adjacent electrode active materials requires a longer carbon nanotube cluster. In addition, the longer the average length, the more electrode active materials are connected and the more conductive paths there are. Therefore, the average length of the carbon nanotube cluster should not be less than 0.2 times the particle size of the electrode active material in order to form a complete conductive network in the electrode active material layer.

[0069] It should be noted that, in this application, the particle size Dv50 of the electrode active material has a meaning known in the art. Dv50 indicates that, in the volume-based particle size distribution of the electrode active material, 50% of the particles have a particle size smaller than this value. The particle size Dv50 of the electrode active material can be determined using methods and instruments known in the art. For example, it can be determined using a laser particle size analyzer (e.g., Malvern Mastersizer 2000E) according to GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method.

[0070] The electrode provided in this application may include a current collector. This application does not limit the current collector; it may use metal foil, porous metal plate, or composite current collector. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.). As an example, the electrode is the positive electrode of a lithium-ion battery, and the positive electrode current collector is aluminum foil.

[0071] In some embodiments, the current collector has two surfaces opposite each other in its thickness direction, and the electrode active material layer can be disposed on one surface of the current collector or on both surfaces simultaneously. For example, the current collector has two surfaces opposite each other in its thickness direction, and the negative electrode active material layer is disposed on any one or both surfaces of the opposite surfaces of the current collector.

[0072] In some embodiments, the electrode active material may be a positive or negative active material commonly used in the art, and there are no particular limitations on the specific type.

[0073] For example, the positive electrode active material may use one or more selected from the group consisting of lithium transition metal oxides, lithium-containing phosphates with an olivine structure, and modified compounds of each of the foregoing. The modified compound of each of the above positive electrode active materials may be a product obtained by doping modification, surface coating modification, or both doping and surface coating modification of the positive electrode active material. By way of example, the lithium transition metal oxide may include one or more selected from the group consisting of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof. By way of example, the lithium-containing phosphate with an olivine structure may include one or more selected from the group consisting of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, a composite material of lithium manganese iron phosphate and carbon, and modified compounds thereof. These positive electrode active materials may be used alone in only one kind, or two or more kinds may be used in combination.

[0074] The negative electrode active material may use one or more selected from the group consisting of carbonaceous materials, metal compounds alloyable with lithium, metal oxides that may be doped with lithium or undoped with lithium, and composites comprising a metal compound and a carbonaceous material. By way of example, the carbonaceous material may include one or more selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fibers and amorphous carbon; the metal compounds alloyable with lithium may include one or more selected from the group consisting of silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloys, Sn alloys and Al alloys; the metal oxides that may be doped with lithium or undoped with lithium may include one or more selected from the group consisting of SiOv (0<v<2), SnO2, vanadium oxides and lithium vanadium oxides; the composite comprising a metal compound and a carbonaceous material may comprise Si-C composites and / or Sn-C composites. These negative electrode active materials may be used alone in only one kind, or two or more kinds may be used in combination.

[0075] In some embodiments, the conductive agent may further include a second conductive agent, wherein the second conductive agent may include one or more selected from the group consisting of conductive carbon black, acetylene black, discrete carbon nanotubes, carbon fibers, Ketjen black and graphene, and the mass percentage of the second conductive agent in the electrode active material layer is 0.05% to 5%.

[0076] In some of the above embodiments, a second conductive agent can be added on the basis of using carbon nanotube clusters as a conductive agent. The function of this is that the carbon nanotube clusters and the second conductive agent can form a composite conductive network together, which has a more stable structure and can still exist stably even during repeated charge and discharge. In addition, the carbon nanotube clusters mainly ensure the long-range electronic conduction path, while the second conductive agent can collect the microcurrent of the electrode active material and ensure the short-range electronic conduction path. The two work together to further improve the conductivity of the electrode, prevent polarization, and improve electrical performance.

[0077] The second conductive agent can be one of the commonly used conductive agents in the prior art. Point-type conductive agents, such as carbon black, can further reduce the electrode resistance and suppress damage to the electrode active material during electrode winding. Area-type conductive agents, such as graphene, can form a denser conductive network with carbon nanotube clusters, thereby further improving the electrode's conductivity. Linear conductive agents, such as carbon nanotubes, can effectively collect microcurrents from the electrode active material while ensuring short-range electronic conduction pathways, thus improving the electrode's conductivity. Therefore, those skilled in the art can select one or more of the above materials as needed.

[0078] Those skilled in the art can control the mass percentage of the second conductive agent in the electrode active material layer to be between 0.05% and 5%, depending on the actual situation. For example, the mass percentage of the second conductive agent in the electrode active material layer can be 0.05%, 0.1%, 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or within any range of the above values.

[0079] In some embodiments, the electrode active material layer may further include a binder, wherein the binder comprises 0.5% to 10% by mass in the electrode active material layer. The binder is used to ensure adhesion between electrode active material particles or between the electrode active material and the current collector. Common binders used in the art can be used, and their type is not particularly limited. The binder may, for example, include one or more of the following: polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinyl alcohol, polyacrylonitrile, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, carboxymethyl cellulose, styrene-butadiene rubber, fluororubber, or various copolymers thereof. These binders may be used alone or in combination of two or more.

[0080] Furthermore, the amount of binder added can be adjusted based on actual needs. Those skilled in the art can minimize the amount of binder added while ensuring adhesion between electrode active material particles or between the electrode active material and the current collector, thereby guaranteeing the energy density of the electrode. Generally, the mass percentage of binder in the electrode active material layer is 0.5% to 10%. For example, the mass percentage of binder in the electrode active material layer can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, or any range of the above values.

[0081] In some embodiments, the porosity k of the electrode active material layer satisfies 10% ≤ k ≤ 35%. For example, the porosity k can be 10%, 15%, 20%, 25%, 30%, 35%, or within any of the above values.

[0082] In some of the above embodiments, the coated electrode active material layer is loose and porous, with large pores between various particles. This has an adverse effect on battery performance. Therefore, the coated electrode needs to be rolled to give the electrode active material a suitable porosity. If the porosity is too high, the particles inside the electrode are not in close contact, resulting in longer ion and electron transport paths and greater resistance, causing significant energy loss. Conversely, if the porosity is too low, the electrolyte is not easily wetted, leading to difficulties in ion transport and reduced cycle performance and rate capability of the battery cell. This application uses carbon nanotube clusters as a conductive agent, which can form a conductive network with good conductivity in the electrode active material layer. This network can stably connect the electrode active material and provide a stable conductive path. Therefore, the porosity of the electrode active material layer can be appropriately increased, thereby improving the electrolyte wettability of the electrode, increasing ionic conductivity, reducing cycle decay caused by electrode polarization, and extending the battery cell's lifespan. The choice of porosity is related to the amount of carbon nanotube clusters added, their aspect ratio, and the amount and particle size of the electrode active material added. In some embodiments of this application, controlling the porosity k of the electrode active material layer to 10% ≤ k ≤ 35% results in better conductivity. More preferably, k satisfies 15% ≤ k ≤ 30%.

[0083] It should be noted that in this application, the porosity k of the electrode active material layer has a meaning known in the art, and the porosity k of the electrode active material layer can be measured using methods and instruments known in the art. For example, pores are the interparticle spacing of a material, and porosity refers to the percentage of pore volume in a material to the total volume of the material in its natural state. Porosity can be tested by the following method: First, the electrode is punched into a circular disc with a diameter of 10 mm or 14 mm, with a smooth surface, no gaps, and no powder shedding. The number of small discs is greater than 40. The thickness of the first active material layer and the second active material layer can be obtained by scanning the cross-section with an electron microscope. Then, the two layers with different porosities are cut apart according to the thickness of each layer, cleaned with dimethyl carbonate and dried, and then tested using a gas displacement method to obtain the porosity of different electrode active material layers.

[0084] In some embodiments, the porosity k of the electrode active material layer, the average length L of the carbon nanotube cluster, and the average diameter D satisfy: L / D×k≥0.5.

[0085] In some of the above embodiments, the relationship between the aspect ratio of the carbon nanotube clusters and the porosity k of the electrode active material layer is further defined. A higher aspect ratio of the carbon nanotube clusters is more conducive to the formation of a three-dimensional conductive network, thereby improving the electronic conduction path and enhancing the electrode's conductivity. A larger porosity, on the other hand, is beneficial for improving the electrolyte wettability of the electrode, thereby increasing the electrode's ionic conductivity. Therefore, when the product of the aspect ratio and porosity of the carbon nanotube clusters is not less than 0.5, electrode polarization can be effectively reduced, thereby improving the electrode's rate performance and cycle performance, and extending the battery cell's lifespan. More preferably, 0.8 ≤ L / D × k ≤ 1.6.

[0086] Methods for manufacturing electrodes

[0087] This application also provides a method for manufacturing an electrode, which may include the following steps:

[0088] S10 was used to prepare dispersions of carbon nanotube clusters;

[0089] S20 adds carbon nanotube cluster dispersion and electrode active material to a solvent to prepare electrode active material slurry.

[0090] In some embodiments, step S10 may specifically include:

[0091] S11 adds conventional carbon nanotube raw materials and dispersants to a dispersion medium to obtain a mixed solution;

[0092] S12 disperses conventional carbon nanotube raw materials by applying shear force to a mixed solution to obtain a dispersion of carbon nanotube clusters.

[0093] In some embodiments, in step S11, the dispersion medium may include dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol, or octanol; diols, such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-dimethylpropanol, etc. One or more of the following dispersion media are used: propylene glycol, 1,3-butanediol, 1,5-pentanediol, hexanediol, glycerol, trimethylolpropane, pentaerythritol, sorbitol, ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, acetone, methyl ethyl ketone, methyl propyl ketone, cyclopentanone, ethyl acetate, γ-butyrolactone, and ε-propiolactone. These dispersion media can be used alone or in combination of two or more. As an example, the dispersion media can be N-methylpyrrolidone (NMP). Conventional carbon nanotube raw materials and carbon nanotube clusters exhibit good dispersibility in the above dispersion media.

[0094] In some embodiments, in step S11, the dispersant may include one or more of hydrogenated nitrile butadiene rubber, polyvinylidene fluoride, and carboxymethyl cellulose. As an example, the dispersant may be hydrogenated nitrile butadiene rubber. Dispersants can improve the dispersion stability of conventional carbon nanotube raw materials and carbon nanotube clusters in a dispersion medium.

[0095] In some embodiments, in step S11, the conventional carbon nanotube raw material can be a bonded body or aggregate of carbon nanotube units. As an example, the conventional carbon nanotube raw material can be an aggregate of multi-walled carbon nanotube units.

[0096] In some embodiments, in step S11, the mass percentage of conventional carbon nanotube raw material in the mixed solution can be 1% to 4%. Under these conditions, the conventional carbon nanotube raw material is dispersed at an appropriate level in the mixed solution to form carbon nanotube clusters of appropriate size. As an example, the mass percentage of conventional carbon nanotube raw material in the mixed solution can be 1.5%.

[0097] In some embodiments, in step S11, the mass ratio of conventional carbon nanotube raw material to dispersant can be from 1:0.1 to 10. Under these conditions, the conventional carbon nanotube raw material is dispersed at an appropriate level in the mixed solution to form carbon nanotube clusters of appropriate size, while improving the dispersion stability of the carbon nanotube clusters. As an example, the mass ratio of conventional carbon nanotube raw material to dispersant can be 1:2.

[0098] In some embodiments, in step S11, the solid content in the mixed solution is 1.5 wt% to 20 wt%. Under these conditions, conventional carbon nanotube raw materials are dispersed at an appropriate level in the mixed solution to form carbon nanotube clusters of appropriate size, while improving the dispersion stability of the carbon nanotube clusters.

[0099] In some embodiments, in step S12, a dispersion of carbon nanotube clusters can be obtained by applying shear force to the mixed solution using a mixing device or ultrasonic dispersion equipment such as a homogenizer, bead mill, ball mill, sand mill, basket mill, grinder, universal stirrer, transparent mixer, spike mill, TK mixer, or a mixture device. Specifically, ball milling can be used to control the diameter of the carbon nanotube clusters, thereby obtaining carbon nanotube clusters that meet the requirements of any embodiment of the first aspect of this application.

[0100] In some embodiments, step S12 may specifically include: adding the mixed solution to a container containing grinding balls, and rotating the container to obtain a dispersion of carbon nanotube clusters.

[0101] The average diameter of the grinding balls can be 0.5 to 2.5 mm, the rotation speed of the container can be 500 to 6000 rpm, and the grinding time can be 0.5 to 2 hours. Under these conditions, the structure of the carbon nanotube units can be preserved, and the diameter of the carbon nanotube clusters can be appropriately controlled. The grinding time refers to the total time spent using the grinding balls; for example, if multiple grinding operations are performed, the grinding time refers to the total time of all operations.

[0102] The ball milling conditions described above are used to appropriately disperse conventional carbon nanotube raw materials, particularly excluding conditions for dispersing conventional carbon nanotube raw materials into carbon nanotube clusters or single-chain carbon nanotubes with a diameter not exceeding 0.2 μm. In other words, the ball milling conditions are used to appropriately disperse conventional carbon nanotube raw materials to form carbon nanotube clusters with a diameter greater than 0.2 μm, in which carbon nanotube units are bonded together side-by-side. This can only be achieved by strictly controlling the composition of the mixed solution and the conditions of the dispersion process.

[0103] It should be noted that the average diameter of carbon nanotube clusters is mainly controlled by the average diameter of the grinding balls, the rotation speed, and the milling time. Generally speaking, appropriately increasing the diameter of the grinding balls and decreasing the rotation speed and milling time can increase the average diameter of the carbon nanotube clusters while still dispersing conventional carbon nanotube raw materials. Furthermore, the average length of the carbon nanotube clusters is mainly determined by the length of the carbon nanotube units in the conventional carbon nanotube raw materials. Those skilled in the art can make appropriate selections and adjustments as needed.

[0104] In some embodiments, in step S20, a second conductive agent and / or binder may be added to the electrode active material slurry. It should be noted that the electrode active material, the second conductive agent, and the binder can be selected with reference to the embodiments of the first aspect. Solvents may include dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), N-methylpyrrolidone (NMP), such as methanol, ethanol, 1-propanol, 2-propanol (isopropanol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol, or octanol; diols, such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,3- One or more of the following solvents are used: butanediol, 1,5-pentanediol, hexanediol, glycerol, trimethylolpropane, pentaerythritol, sorbitol, ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monobutyl ether, acetone, methyl ethyl ketone, methyl propyl ketone, cyclopentanone, ethyl acetate, γ-butyrolactone, and ε-propiolactone. These solvents may be used alone or in combination. The solvent may be the same as or different from the dispersion medium. As an example, the solvent may be N-methylpyrrolidone (NMP).

[0105] In some embodiments, the solid content in the electrode active material slurry is 50 wt% to 80 wt%.

[0106] The electrode preparation method may further include drying an electrode active material slurry to obtain an electrode active material layer. Specifically, the electrode active material layer can be formed by coating the electrode active material slurry onto a current collector and then drying the coated current collector, or by casting the electrode active material slurry onto a separate carrier and then pressing the film layer separated from the carrier onto the current collector. If necessary, a rolling process can be further performed after forming the electrode active material layer by the above methods. In this case, considering the physical properties of the finally prepared electrode, drying and rolling can be performed under appropriate conditions without particular limitation.

[0107] Secondary batteries

[0108] A second aspect of this application provides a secondary battery, comprising: a positive electrode, a negative electrode, a separator, and an electrolyte;

[0109] Wherein, at least one of the positive electrode and the negative electrode is an electrode according to any embodiment of the first aspect.

[0110] According to this application, at least one of the positive or negative electrodes of the secondary battery is an electrode as described in any embodiment of the first aspect. The embodiments of the electrodes have been described and illustrated in detail above, and will not be repeated here. It is understood that the secondary battery of this application can achieve the beneficial effects of any of the above-described embodiments of the electrodes of this application.

[0111] In some embodiments, the positive electrode is the electrode according to any embodiment of the first aspect.

[0112] In some embodiments, the resistance of the positive electrode of the secondary battery is R0 when it is at 0% SOC, and the resistance of the positive electrode of the secondary battery is R when it is at 100% SOC. 100 ,

[0113] Among them, R0 and R1 00 Satisfy: (R0 - R 100 ) / R0≤30%.

[0114] In some of the above embodiments, due to different states of charge of the secondary battery electrodes, the volume of the electrode active material in the electrode active material layer changes, which affects the conductive network of the electrode active material layer. This leads to a significant change in the electrode resistance, increasing polarization and affecting the battery cell's lifespan. Therefore, it can be understood that the more stable the conductive network formed by the conductive agent, the smaller the rate of change in electrode resistance, the smaller the polarization, and the longer the battery cell's lifespan. When using the electrode of the first aspect embodiment of this application as the positive electrode, the rate of change in resistance of the positive electrode under different states of charge can not exceed 30%. Using the carbon nanotube clusters of the first aspect embodiment as the conductive agent can form a stable conductive network with good conductivity. Therefore, the electrode conductivity is less affected by the volume change of the electrode active material during charging and discharging, thereby significantly reducing the rate of change in electrode resistance, reducing polarization, and improving the battery cell's lifespan.

[0115] [Septum]

[0116] The separator is positioned between the positive and negative electrodes, primarily serving to prevent short circuits between them while allowing active ions to pass through. This application does not impose any particular restriction on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.

[0117] In some embodiments, the diaphragm material may be selected from one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride, but is not limited to these. Optionally, the diaphragm material may include polyethylene and / or polypropylene. The diaphragm may be a single-layer film or a multi-layer composite film. When the diaphragm is a multi-layer composite film, the materials of each layer may be the same or different. In some embodiments, a ceramic coating or a metal oxide coating may also be provided on the diaphragm.

[0118] Electrolyte

[0119] The electrolyte acts as a conductor of active ions between the positive and negative electrodes. The electrolyte used in the secondary application of this invention can be any electrolyte known in the prior art.

[0120] In some embodiments, the electrolyte may include an organic solvent, an electrolyte salt, and optional additives. The types of organic solvents, lithium salts, and additives are not specifically limited and can be selected as needed.

[0121] In some embodiments, the electrochemical device is a lithium-ion battery, and the electrolyte salt may include a lithium salt. As examples, the lithium salt includes, but is not limited to, at least one of LiPF6 (lithium hexafluorophosphate), LiBF6 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalate borate), LiBOB (lithium dicoxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorodioxalate phosphate), and LiTFOP (lithium tetrafluorooxalate phosphate). One of the above lithium salts may be used alone, or two or more may be used simultaneously.

[0122] In some embodiments, the electrochemical device is a sodium-ion battery, and the electrolyte salt may include a sodium salt. As an example, the sodium salt may be selected from at least one of NaPF6, NaClO4, NaBCl4, NaSO3CF3, and Na(CH3)C6H4SO3.

[0123] In some embodiments, as examples, the organic solvent includes, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE). One of the above organic solvents may be used alone, or two or more may be used simultaneously. Optionally, two or more of the above organic solvents may be used simultaneously.

[0124] In some embodiments, the additive may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.

[0125] As an example, the additives include, but are not limited to, at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), vinyl sulfate (DTD), propylene sulfate, vinyl sulfite (ES), 1,3-propanesulfonate lactone (PS), 1,3-propenesulfonate lactone (PST), sulfonate cyclic quaternary ammonium salts, succinic anhydride, succinic anhydride (SN), adiponitrile (AND), tris(trimethylsilane) phosphate (TMSP), and tris(trimethylsilane) borate (TMSB).

[0126] The electrolyte can be prepared according to conventional methods in the art. For example, an organic solvent, an electrolyte salt, and optional additives can be mixed evenly to obtain an electrolyte. There are no particular restrictions on the order of addition of the materials; for example, the electrolyte salt and optional additives can be added to the organic solvent and mixed evenly to obtain an electrolyte; or, the electrolyte salt can be added to the organic solvent first, and then the optional additives can be added to the organic solvent and mixed evenly to obtain an electrolyte.

[0127] electronic devices

[0128] A third aspect of this application provides an electronic device, including the secondary battery of the second aspect of this application.

[0129] The electronic device described in this application is not particularly limited and can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors, etc.

[0130] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0131] Preparation of dispersions of carbon nanotube clusters:

[0132] A mixed solution was prepared by mixing conventional multi-walled carbon nanotube raw materials composed of multi-walled carbon nanotube units with an average diameter of more than 3 nm and an average length of more than 3 μm with hydrogenated nitrile butadiene rubber in NMP. The solid content in the mixed solution was 1.5 wt% to 20 wt%, and the mass ratio of conventional multi-walled carbon nanotube raw materials to hydrogenated nitrile butadiene rubber was 1:0.1 to 10.

[0133] The mixed solution is added to a container containing grinding balls, and the container is rotated to obtain a dispersion of carbon nanotube clusters. The average diameter of the grinding balls can be 0.5 to 2.5 mm, the rotation speed of the container can be 500 to 6000 rpm, and the grinding time can be 0.5 to 2 h.

[0134] By controlling the specifications of conventional multi-walled carbon nanotube raw materials and the ball milling conditions, dispersions of carbon nanotube clusters of different specifications were obtained for later use.

[0135] Lithium-ion battery charging rate test (i.e., high-rate charging time): Take the finished battery cell, discharge it at 0.7C to the set value at 25℃ (3.0V for LCO positive electrode active material); then charge it at 6C to the cutoff voltage, and then charge it at the cutoff voltage to 0.05C. Record the time of the entire charging process as T.

[0136] Lithium-ion batteries at 25°C, steady-state internal resistance (Fresh Rss) after a single cycle and steady-state impedance (Rcc) growth rate after 500 cycles:

[0137] Take the finished battery cells and perform the following tests at (25±3)℃:

[0138] a. Let stand for 2 hours, fully charge at 0.5C to the cutoff voltage, then charge at the cutoff voltage to 0.025C, and let stand for 10 minutes.

[0139] b. Discharge at 0.2C to the set value (3.0V for LCO positive electrode active material). The discharge capacity in this step is recorded as Cl. Let stand for 5 minutes.

[0140] c. Test the cell's Chem.ID (depth of discharge (DOD)-voltage curve) at a discharge rate of 0.1C1, including the point: voltage V0 at 80% DOD.

[0141] d. {Charge at 1.5C to the cutoff voltage, then charge at the cutoff voltage to 0.05C; let stand for 5 minutes; discharge 80% of the rated capacity at a rate of 0.7C, record the voltage at this point as V1, the cell internal resistance Rcc1 = (V1 - V0) / 0.7C, continue discharging to the set value (3.0V for LCO positive electrode material), let stand for 5 minutes;}

[0142] The process in the loop [ ] is repeated 49 times, and the internal resistance of the cell after discharging 80% of the rated capacity is recorded sequentially as Rcc1 / Rcc2...Rcc49; in the 50th cycle, it is charged at 0.5C to the cutoff voltage, and then charged at the cutoff voltage to 0.05C; it is left to stand for 5 minutes; then it is discharged at 0.7C to the set value, and the internal resistance of the cell after discharging 80% of the rated capacity is recorded as Rcc50.

[0143] The loop {} executes 10 times + [ ] 1 time.

[0144] e. Fresh Rss is Rcc1. The steady-state internal resistance growth rate at 500 cycles is (Rcc501 / Rcc3-100%).

[0145] Lithium-ion battery positive electrode resistance tests at 0% SOC and 100% SOC:

[0146] Take the finished battery cells and perform the following tests at (25±3)℃:

[0147] 1) Let stand for 2 hours, then discharge at 0.2C to the full discharge set value (3.0V for LCO positive electrode active material), let stand for 5 minutes; charge at 0.5C to the cutoff voltage, then charge at the cutoff voltage to 0.02C; let stand for 5 minutes.

[0148] 2) Discharge to the full discharge set value at 0.1C, and record the cutoff capacity of this step as C1;

[0149] 3) Charge at 0.5C1 to the cutoff voltage, then charge at the cutoff voltage to 0.02C1;

[0150] 4) a. Discharge 0.5C1 until the remaining capacity is 80% C1, then let stand for 30 minutes;

[0151] b. Disassemble the battery to obtain the positive electrode plate, and dry it in an environment with humidity ≤15% for 30 minutes;

[0152] c. Use a diaphragm resistance meter to test the resistance of the positive electrode. Test at ≥15 test positions and record the average resistance at all test positions as the resistance of the positive electrode at 80% SOC.

[0153] d. Use the same methods as a to c to test the resistance of the positive electrode when the cell is discharged to 0% of its remaining capacity.

[0154] Example 1

[0155] Preparation of the positive electrode:

[0156] A positive electrode active material, a dispersion of carbon nanotube clusters, and polyvinylidene fluoride were mixed in NMP at a mass ratio of 97:1.4:1.6 to obtain a positive electrode active slurry. The positive electrode active material was lithium cobalt oxide (LCO) with a particle size Dv50 of 15 μm. The solid content of the positive electrode active slurry was 72 wt%. The average diameter, average length, and average diameter of the carbon nanotube cluster units contained therein are shown in Table 1. The positive electrode active slurry was coated on aluminum foil, and the aluminum foil was dried at 95 °C. After cold pressing, cutting, and slitting, it was dried under vacuum at 85 °C for 4 h to obtain a positive electrode with a porosity of 20%.

[0157] Preparation of the negative electrode:

[0158] A negative electrode active slurry was prepared by mixing artificial graphite negative electrode active material, conductive agent Super P, thickener sodium carboxymethyl cellulose (CMC), and binder styrene-butadiene rubber (SBR) in deionized water at a mass ratio of 96.4:1.5:0.5:1.6, with a solid content of 54 wt%. The negative electrode active slurry was coated onto copper foil, which was dried at 85°C. After cold pressing, cutting, and slitting, the copper foil was dried under vacuum at 80°C for 12 hours to obtain the negative electrode.

[0159] Electrolyte preparation: A conventional 1.5 mol / L lithium hexafluorophosphate electrolyte was selected.

[0160] Preparation of the separator membrane: A 7μm thick polyethylene (PE) separator membrane substrate was coated with a 3μm ceramic coating.

[0161] The preparation of lithium-ion batteries involves stacking the positive electrode, separator, and negative electrode in sequence, with the separator acting as a barrier between the positive and negative electrodes. The cells are then wound to obtain bare cells. After welding the tabs, the bare cells are placed in an outer packaging foil aluminum-plastic film. The prepared electrolyte is injected into the dried bare cells. The cells undergo vacuum sealing, settling, formation (0.02C constant current charging to 3.3V, then 0.1C constant current charging to 3.6V), shaping, and capacity testing to obtain a soft-pack lithium-ion battery.

[0162] Examples 2 to 19

[0163] The preparation of the positive electrode is similar to that in Example 1, except that the average diameter, average length and average diameter of the carbon nanotube clusters and the carbon nanotube cluster units contained therein are different, as shown in Table 1.

[0164] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0165] Comparative Example 1

[0166] The preparation of the positive electrode is similar to that in Example 1, except that single-chain multi-walled carbon nanotubes (obtained by complete dispersion of conventional multi-walled carbon nanotube raw materials) are used instead of carbon nanotube clusters. The average diameter of the single-chain multi-walled carbon nanotubes is shown in Table 1.

[0167] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0168] Comparative Example 2

[0169] The preparation of the positive electrode is similar to that in Example 1, except that single-chain single-walled carbon nanotubes (obtained by complete dispersion of conventional single-walled carbon nanotube raw materials) are used instead of carbon nanotube clusters. The average diameter of the single-chain single-walled carbon nanotubes is shown in Table 1.

[0170] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0171] Comparative Example 3

[0172] The preparation of the positive electrode is similar to that in Example 1, except that single-walled carbon nanotube clusters (made from conventional single-walled carbon nanotube raw materials instead of conventional multi-walled carbon nanotube raw materials) are used instead of carbon nanotube clusters. The average diameter, average length and average diameter of the carbon nanotube cluster units contained therein are shown in Table 1.

[0173] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0174] Performance testing

[0175] The lithium-ion batteries obtained in Examples 1 to 19 and Comparative Examples 1 to 3 were subjected to the following tests: charging rate test and Rcc growth rate test after 500 cycles. The results are shown in Table 1.

[0176] Table 1

[0177] As shown in Table 1, the charging rate and cycle performance of the lithium-ion batteries prepared in each embodiment are significantly better than those in the comparative example. This indicates that the carbon nanotube clusters used as conductive agents in each embodiment can form a stable conductive network in the electrode, resulting in good conductivity. Furthermore, the Rcc growth rate of the lithium-ion battery at 25°C @ 500cls also demonstrates that the conductive network formed by the carbon nanotube clusters can suppress the volume change of the active material in the electrode during charging and discharging, and the conductive network can effectively reduce the impact of the volume change of the active material on the electrode's conductivity. It is worth noting that the lithium-ion battery in Comparative Example 3, which uses a bundled arrangement of single-walled carbon nanotube units, exhibits poor performance. This may be because the small diameter and high flexibility of single-walled carbon nanotube units make it difficult to obtain carbon nanotube structures with larger diameters. Such structures are also highly flexible and prone to clumping and entanglement, making it difficult to form a stable long-range conductive network. Therefore, the performance of this lithium-ion battery is poor.

[0178] In addition, comparing Examples 1 to 8, it can be seen that the average length of the carbon nanotube cluster has a certain impact on the charging rate and cycle performance. When the average length is 20 μm, the corresponding lithium-ion battery has the best performance. This may be because as the length of the carbon nanotube increases, the long-range conductive network formed becomes more stable and the conductivity is better. However, if the length is too long, the carbon nanotube cluster may be unevenly distributed in the electrode, resulting in some areas of the electrode not being covered by the conductive network, which leads to a decrease in performance.

[0179] Comparing Examples 4, 9 to 13, it can be seen that the average diameter of the carbon nanotube clusters has a certain impact on the charging rate and cycle performance. The performance is best when the average diameter is above 2 μm, and further increases have little impact on the performance of lithium-ion batteries. It is worth noting that the average diameter of the carbon nanotube clusters in Example 9 is 0.2 μm. This is because the diameter of the carbon nanotube clusters in this example is all around 0.2 μm. Although the diameter of the carbon nanotube clusters protected in this application should be greater than 0.2 μm, for comparison purposes, structures composed of bundles of multi-walled carbon nanotube units with a diameter of 0.18 μm or more are all considered as carbon nanotube clusters, and the calculated average diameter is 0.2 μm.

[0180] Comparing Examples 4, 14 to 19, it can be seen that the average diameter of the carbon nanotube units that make up the carbon nanotube clusters also has a certain impact on the performance of lithium batteries. When the average diameter of the carbon nanotube units is between 5 and 10 nm, the performance of lithium-ion batteries is the best. This may be because if the diameter of the carbon nanotube units is too small, the resulting carbon nanotube clusters are not arranged side by side, but are formed by entanglement, which will affect the conductivity of the carbon nanotube clusters. If the diameter is too large, the electronic conductivity path is relatively reduced, which will also affect the conductivity of the carbon nanotube clusters.

[0181] Example 20

[0182] The preparation of the positive electrode is similar to that in Example 4, except that the positive electrode active material is lithium nickel cobalt manganese oxide (NCM) with a particle size Dv50 of 15 μm.

[0183] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0184] Example 21

[0185] The preparation of the positive electrode is similar to that in Example 9, except that the positive electrode active material is lithium manganese oxide (LMO) with a particle size Dv50 of 15 μm.

[0186] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0187] Example 22

[0188] The preparation of the positive electrode is similar to that in Example 12, except that the positive electrode active material is a mixture of lithium cobalt oxide (LCO) and lithium nickel cobalt manganese oxide (NCM) with a particle size Dv50 of 15 μm and a mass ratio of 1:1.

[0189] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0190] Comparative Example 4

[0191] The preparation of the positive electrode is similar to that of Comparative Example 2, except that the positive electrode active material is lithium nickel cobalt manganese oxide (NCM) with a particle size Dv50 of 15 μm.

[0192] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0193] Comparative Example 5

[0194] The preparation of the positive electrode is similar to that of Comparative Example 3, except that the positive electrode active material is lithium manganese oxide (LMO) with a particle size Dv50 of 15 μm.

[0195] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0196] Comparative Example 6

[0197] The preparation of the positive electrode is similar to that of Comparative Example 3, except that the positive electrode active material is a mixture of lithium cobalt oxide (LCO) and lithium nickel cobalt manganese oxide (NCM) with a particle size Dv50 of 15 μm and a mass ratio of 1:1.

[0198] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0199] Performance testing:

[0200] The lithium-ion batteries obtained in Examples 1 to 3, 20 to 22 and Comparative Examples 1, 4 to 6 were tested for positive electrode resistance R0 at 0% SOC and positive electrode resistance R at 100% SOC. 100 The test results are shown in Table 2.

[0201] Table 2 Example 1 LCO 0.22 0.16 26 Example 2 LCO 0.18 0.15 17 Example 3 LCO 0.16 0.15 9 Example 20 NCM 0.53 0.42 21 Example 21 LMO 0.45 0.34 24 Example 22 LCO+NCM 0.32 0.26 19 Comparative Example 1 LCO 0.54 0.30 45 Comparative Example 4 NCM 0.63 0.42 33 Comparative Example 5 LMO 0.58 0.37 36 Comparative Example 6 LCO+NCM 0.45 0.29 36

[0202] As shown in Table 2, for different types of positive electrode active materials, using carbon nanotube clusters as a conductive agent, the change rate of positive electrode resistance under different states of charge does not exceed 30%, demonstrating a significant improvement over the comparative studies. This indicates that the carbon nanotube clusters provided in this application can reduce the impact of state of charge on electrode resistance by forming a stable conductive network for various existing positive electrode active materials, thereby reducing polarization and improving the lifespan of lithium-ion batteries.

[0203] Example 23

[0204] The preparation of the positive electrode is similar to that in Example 1, except that the average diameter and average length of the carbon nanotube clusters are different, as shown in Table 3.

[0205] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0206] Example 24

[0207] The preparation of the positive electrode is similar to that in Example 1, except that the average diameter and average length of the carbon nanotube clusters are different, as shown in Table 3.

[0208] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0209] Example 25

[0210] The preparation of the positive electrode is similar to that in Example 1, except that the average diameter and average length of the carbon nanotube clusters are different, as shown in Table 3.

[0211] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0212] Example 26

[0213] The preparation of the positive electrode is similar to that in Example 1, except that the average diameter and average length of the carbon nanotube clusters are different, as shown in Table 3.

[0214] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0215] Example 27

[0216] The preparation of the positive electrode is similar to that in Example 1, except that the average diameter and average length of the carbon nanotube clusters are different, as shown in Table 3.

[0217] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0218] Example 28

[0219] The preparation of the positive electrode is similar to that in Example 1, except that the average diameter and average length of the carbon nanotube clusters are different, as shown in Table 3.

[0220] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0221] Example 29

[0222] The preparation of the positive electrode is similar to that in Example 27, except that the porosity is different, which is 10%, as shown in Table 3.

[0223] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0224] Example 30

[0225] The preparation of the positive electrode is similar to that in Example 27, except that the porosity is different, which is 15%, as shown in Table 3.

[0226] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0227] Example 31

[0228] The preparation of the positive electrode is similar to that in Example 27, except that the porosity is different, which is 30%, as shown in Table 3.

[0229] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0230] Example 32

[0231] The preparation of the positive electrode is similar to that in Example 27, except that the porosity is different, which is 35%, as shown in Table 3.

[0232] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1.

[0233] Performance testing:

[0234] Fresh Rss tests were performed on the positive electrodes of the lithium-ion batteries obtained in Examples 23 to 32 and Comparative Example 1, and the results are shown in Table 3.

[0235] Table 3

[0236] As can be seen from the results in Table 3, by comparing Examples 23 to 28 and Comparative Example 1, it can be seen that under the condition of constant porosity, the larger the aspect ratio of the carbon nanotube cluster, the smaller the resistance of the positive electrode. The reason may be that the higher aspect ratio of the carbon nanotube cluster is more conducive to the formation of a three-dimensional conductive network, thereby improving the electronic conduction path and enhancing the conductivity of the electrode.

[0237] Comparative examples 27, 29 to 32 show that carbon nanotube clusters with a larger aspect ratio can directly form a stable three-dimensional conductive network, thus the porosity of the positive electrode can be appropriately increased. A larger porosity is beneficial to improving the electrolyte wettability of the electrode, thereby improving the ionic conductivity of the electrode. However, the porosity should not be too large, preferably not exceeding 30%.

[0238] Examples 33 to 41

[0239] The preparation of the positive electrode is similar to that in Example 1, except that the average length of the carbon nanotube clusters and / or the particle size Dv50 of the positive electrode active material lithium cobalt oxide are different, as shown in Table 4.

[0240] The preparation of the negative electrode, electrolyte, separator, and lithium-ion battery is the same as in Example 1. Performance testing

[0241] The lithium-ion batteries obtained in Examples 33 to 41 were subjected to the following tests: charging rate test and Rcc growth rate test after 500 cycles. The results are shown in Table 4. The results of Examples 1, 2 and 4 in Table 1 are also recorded in Table 4 for comparison.

[0242] Table 4

[0243] As shown in Table 4, when the average length of the carbon nanotube clusters in the examples needs to be no less than 0.2 times the particle size of the positive electrode active material, the charging performance and cycle performance are better. This is because the main function of the conductive network formed by the carbon nanotube clusters is to conduct electron transfer between the active materials. Therefore, the conductivity of the electrode is significantly related to the average length of the carbon nanotube clusters and the particle size of the positive electrode active material. When the average length of the carbon nanotube clusters is greater than 0.2 times the particle size of the positive electrode active material, the carbon nanotube clusters can form a stable conductive network, thereby reducing electrode polarization and improving the charging performance and cycle performance of the lithium-ion battery.

[0244] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other.

[0245] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or make equivalent substitutions for some of the technical features. However, these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application.

Claims

1. An electrode, comprising: An electrode active material layer, comprising an electrode active material and a conductive agent. The conductive agent includes carbon nanotube clusters, which are composed of multiple bundled carbon nanotube units. The diameter of the carbon nanotube cluster is >0.2μm, and the average diameter D of the carbon nanotube cluster satisfies 0.5μm≤D≤5μm. The porosity k of the electrode active material layer, the average length L and the average diameter D of the carbon nanotube cluster satisfy: 0.8≤L / D×k≤1.6, the porosity k of the electrode active material layer satisfies 10%≤k≤35%, and the average length L of the carbon nanotube cluster ≥3μm.

2. The electrode according to claim 1, wherein, The carbon nanotube clusters in the electrode active material layer account for 0.05% to 5% of the mass.

3. The electrode according to claim 1, wherein, The average diameter d of the carbon nanotube unit satisfies 3nm≤d≤40nm.

4. The electrode according to claim 3, wherein, The average diameter d of the carbon nanotube unit satisfies 5nm≤d≤20nm.

5. The electrode according to claim 4, wherein, The average diameter d of the carbon nanotube unit satisfies 5nm≤d≤10nm.

6. The electrode according to claim 1 or 3, wherein, The carbon nanotube unit is a multi-walled carbon nanotube unit.

7. The electrode according to claim 1, wherein, The average diameter D of the carbon nanotube clusters satisfies 0.5μm≤D≤3μm.

8. The electrode according to claim 1, wherein, The average length L of the carbon nanotube cluster is ≥5 μm.

9. The electrode according to claim 8, wherein, The average length L of the carbon nanotube cluster satisfies 5μm≤L≤30μm.

10. The electrode according to claim 1, wherein, The particle size Dv50 of the electrode active material and the average length L of the carbon nanotube cluster satisfy the following condition: L≥0.2×Dv50.

11. The electrode according to claim 1, wherein, The conductive agent further includes a second conductive agent, which includes one or more of conductive carbon black, acetylene black, carbon nanotubes, carbon fibers, Ketjen black, and graphene, and the second conductive agent has a mass percentage of 0.05% to 5% in the electrode active material layer.

12. The electrode according to claim 1, wherein, The electrode active material layer further includes a binder, wherein the binder comprises 0.5% to 10% by mass in the electrode active material layer.

13. The electrode according to claim 1, wherein, The porosity k of the electrode active material layer satisfies 15% ≤ k ≤ 30%.

14. A secondary battery, comprising: Positive electrode, negative electrode, membrane, and electrolyte; Wherein, at least one of the positive electrode and the negative electrode is an electrode according to any one of claims 1 to 13.

15. The secondary battery according to claim 14, wherein, The positive electrode is the electrode according to any one of claims 1 to 11.

16. The secondary battery according to claim 15, wherein, The resistance of the positive electrode of the secondary battery is R0 when it is at 0% SOC, and the resistance of the positive electrode of the secondary battery is R when it is at 100% SOC. 100 , Among them, R0 and R 100 Satisfy: (R0-R 100 ) / R0≤30%.

17. An electronic device comprising: The secondary battery according to any one of claims 14 to 16.

Citation Information

Patent Citations

  • Conductive material dispersed liquid and lithium secondary battery manufactured using same

    CN107851801A

  • Cathode for secondary battery and secondary battery comprising same

    CN108028355A

  • Secondary battery and electronic device

    CN114300686A